2015
DOI: 10.1177/1087054715616490
|View full text |Cite
|
Sign up to set email alerts
|

Early Visual Foraging in Relationship to Familial Risk for Autism and Hyperactivity/Inattention

Abstract: Objective: Information foraging is atypical in both autism spectrum disorders (ASDs) and ADHD; however, while ASD is associated with restricted exploration and preference for sameness, ADHD is characterized by hyperactivity and increased novelty seeking. Here, we ask whether similar biases are present in visual foraging in younger siblings of children with a diagnosis of ASD with or without additional high levels of hyperactivity and inattention. Method: Fifty-four low-risk controls (LR) and 50 high-risk sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
2
22
0
1
Order By: Relevance
“…A number of prospective studies have reported data that make it more challenging to determine if regression has occurred. These include studies in which only standardized scores [Estes et al, ; Landa, Gross, Stuart, & Bauman, ; Levin, Varcin, O'Leary, Tager‐Flusberg, & Nelson, Lord, Luyster, Guthrie, & Pickles, ] or group data are reported [Barbaro & Dissanayake, ;Caravella & Roberts, ; Chenausky, Nelson, & Tager‐Flusberg, ; Filliter et al, ; Gliga, Smith, Likely, Charman, & Johnson, ; Ibañez, Grantz, & Messinger, ; Iverson et al, ], where loss and plateau are not differentiated [Brian et al, ], or where longitudinal analysis was not carried out [Bedford, et al, ; Gangi et al, ]. Although these studies show progressive divergence from typical development, they cannot differentiate developmental arrest or slowing from regression, and group data may have obscured variability within groups [Elsabbagh & Johnson, ].…”
Section: Evidence For Regression and Prevalence Ratesmentioning
confidence: 99%
“…A number of prospective studies have reported data that make it more challenging to determine if regression has occurred. These include studies in which only standardized scores [Estes et al, ; Landa, Gross, Stuart, & Bauman, ; Levin, Varcin, O'Leary, Tager‐Flusberg, & Nelson, Lord, Luyster, Guthrie, & Pickles, ] or group data are reported [Barbaro & Dissanayake, ;Caravella & Roberts, ; Chenausky, Nelson, & Tager‐Flusberg, ; Filliter et al, ; Gliga, Smith, Likely, Charman, & Johnson, ; Ibañez, Grantz, & Messinger, ; Iverson et al, ], where loss and plateau are not differentiated [Brian et al, ], or where longitudinal analysis was not carried out [Bedford, et al, ; Gangi et al, ]. Although these studies show progressive divergence from typical development, they cannot differentiate developmental arrest or slowing from regression, and group data may have obscured variability within groups [Elsabbagh & Johnson, ].…”
Section: Evidence For Regression and Prevalence Ratesmentioning
confidence: 99%
“…However, revisitations in visual scanning may serve as an early marker of atypical attention development in infants at risk of autism. Gliga, Smith, Gilhooly, Charman, and Johnson (2015) calculated the probability of revisitations by coding up to 10 visits (i.e., the sum of all consecutive fixations within an AOI). However, information about local temporal gaze patterns (i.e., LAM) gets lost by collapsing consecutive fixations into one visit.…”
Section: Average Fixation Duration Versus Rqa Parametersmentioning
confidence: 99%
“…RQA could prove useful for studying visual scanning in atypical development. Children with autism spectrum disorder (ASD) demonstrate high revisitation rates when exploring natural visual scenes (Gliga et al, 2015). Additionally, infant siblings of children with ASD exhibit socio-communicative problems, which could be linked to difficulties with attention disengagement from socially relevant stimuli (Elsabbagh et al, 2013).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, from infancy onwards, a balance between exploitation (of the known) and exploration (of the unknown) is essential for optimal adaptation to the environment so that one is alert to pertinent new information but at the same time can focus on a task at hand (16). If there is a bias towards exploitation or exploration, this could impact optimal foraging and, consequently, learning and adaptive functioning (18).…”
Section: Introductionmentioning
confidence: 99%